Combined Application of Bio-PF and Synthetic Fungicide Suppress Soil Borne Disease Caused by Cylindrocladium sp. in Leather Leaf - Hanudin Hanudin; Wakiah Nuryani; Evi Silvia Yusuf; Kurniawan Budiarto (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2019)
An evaluation of formulated Bio-PF with the active ingredient of Pseudomonas fluorescens to reduce synthetic fungicide usage in controlling soil borne disease in leather leaf fern under different shelters was studied. The research was conducted at the experimental field of the Indonesian Ornamental Crops Research Institute (IOCRI) from January to December 2015. Different concentrations of Bio-PF were singly and/nor alternately applied with two different synthetic fungicides were applied on leather leaf plants under UV plastic + 70% black-net and 70% black-net shelters. The results showed that the average disease intensity was higher in 70% black-net shelter. Weekly alternate-application of Bio-PF 5 + Carbendazim & Mancozeb and single Carbendazim & Mancozeb gave lower disease intensity than other treatments with the highest percentage of suppression. These two treatments also improved yield in terms of number and proportion of the preferred grade of harvested leaves. Combined Bio-PF 5 + Carbendazim & Mancozeb gave longer vase life and the application reduced synthetic fungicide usage in controlling the respected disease. In term of synthetic fungicides, Carbendazim & Mancozeb gave more consistent effects on disease suppression, plant growth and foliage production than Asilbensolar & Mancozeb.